Physiochemical, nutritional and functional characterization of 10 different pear cultivars (Pyrus spp.) (Journal of Applied Botany and Food Quality, 2016)
This study was performed to compare the physiochemical properties and nutritional components including sugars, amino acids, and minerals of 10 common pear cultivars cultivated in Korea (four Pyrus spp.). Furthermore, the pear cultivars were characterized for functional properties with respect to phenolic compounds by HPLC/DAD analysis and antioxidant activities using DPPH and ABTS assays. Among the 10 pear cultivars that were tested, Niitaka and Hanareum pears show the best physiochemical properties such as higher sugar/acid ratio and proper firmness. They also showed relatively enriched soluble sugar (12.6 ~ 13.0 g/100g FW), amino acid (4.5 ~ 7.3 g/100 g DW) or mineral contents with high K/Na ratio. For functional properties, Niitaka and Hanareum pears have significantly higher contents of total phenolics (240 mg/100 g DW), arbutin (103 ~ 124 mg/100 g DW), and chlorogenic acid (11 mg/100 g DW) as well as strong antioxidant activities (49 % or 86 %) among cultivars. These results indicate that Niitaka, and Hanareum cultivars, could be best for consumption or favorable processing due to excellent product quality and high concentrations of nutritional and functional compounds.